ON THE LIFE-HISTORY AND ECOLOGY OF HORNELLIA MARINA GEN. ET SP. NOV., (CHLOROMONADINEAE), CAUSING GREEN DISCOLORATION OF THE SEA AND MORTALITY AMONG MARINE ORGANISMS OFF THE MALABAR COAST - Subramanian, R (Indian Journal of Fisheries, 2016)
THERE are many published accounts dealing with " red ", " yellow " and " pink " discoloration of the sea water, caused by the occurrence in swarms of micro-organisms, particularly members of the Dinophyceae (cf. Hayes and Austin, 1951). Some of these organisms are known to affect the fishery adversely. Green discoloration of the sea, however, has not been recorded frequently.